The Impact of EU Agricultural Policies and Taxes on EU Agricultural Trade (cereals sector) and the European Agriculture Sector (cereals) - Moravska, Mariia (2024)
This study aims to test whether EU-based cereal firms are effectively protected from potential competition and other economic threats. One of the biggest shares of EU budget expenditures is the Common Agriculture Policy, one of the objectives of which is farm income protection. Thus, CAP subsidies aimed at income protection are seen as possible tools that should protect local firms' profitability, along with complimentary taxation measures in the form of import tariff rates for cereals. In order to evaluate the possible relationship, a Fixed Effects regression model with ROA as a dependent variable was employed, using a panel dataset with 3440 observations. The dataset contained the biggest EU-based cereals companies. The data was collected from the Orbis database. Also, sources such as the World Bank, European Commission, Eurostat, and WTO were used to acquire macroeconomic data, tariffs, and CAP data. The obtained regression outcomes demonstrate that firms' profitability is positively correlated with CAP subsidies and negatively correlated with import tariffs.